A review of Psyra Walker, 1860 (Lepidoptera, Geometridae, Ennominae) from China, with description of one new species - Liu, Zulian; Xue, Dayong; Wang, Wenkai; Han, Hongxiang (Zootaxa, 2013)
The genus Psyra Walker, 1860 in China is reviewed. Thirteen species are recognized, of which, P. breviprotrusa sp. nov. is described as new to science, and P. moderata Inoue, 1982, P. gracilis Yazaki, 1992 and P. boarmiata (Graeser, 1892) are recorded for the first time from China. P. cuneata szetschwana Wehrli, 1953 and P. cuneata dsagara Wehrli, 1953 are upgraded to specific level, i.e. P. szetschwana stat. nov. and P. dsagara stat. nov., and a lectotype is designated for P. dsagara. One new synonym is established: P. szetschwana Wehrli, 1953 = P. cuneata lidjangica Wehrli, 1953 syn. nov. The diagnoses for all species are given. Illustrations of external features and genitalia are presented.